2018
DOI: 10.1002/cssc.201801888
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Sulfur Functionalization Anchoring SnO2 and CH3NH3PbI3 for Enhanced Stability and Trap Passivation in Perovskite Solar Cells

Abstract: Trap states at the interface or in bulk perovskite materials critically influence perovskite solar cells performance and long-term stability. Here, a strategy for efficiently passivating charge traps and mitigating interfacial recombination by SnO surface sulfur functionalization is reported, which utilizes xanthate decomposition on the SnO surface at low temperature. The results show that functionalized sulfur atoms can coordinate with under-coordinated Pb ions near the interface. After device fabrication und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…[ 12,13 ] For example, the defects associated with uncoordinated Pb 2+ can induce the deep‐level traps and low built‐in potential, leading to unefficient charge extraction and charge recombination. [ 14–17 ] Furthermore, some crystal defects can drive ion or vacancy to easily migrate in perovskite structures. [ 18 ] Recent study demonstrated the mobile iodine ions (I − ) in the hole‐transporting layer (HTL) and electron‐transporting layer (ETL).…”
Section: Introductionmentioning
confidence: 99%
“…[ 12,13 ] For example, the defects associated with uncoordinated Pb 2+ can induce the deep‐level traps and low built‐in potential, leading to unefficient charge extraction and charge recombination. [ 14–17 ] Furthermore, some crystal defects can drive ion or vacancy to easily migrate in perovskite structures. [ 18 ] Recent study demonstrated the mobile iodine ions (I − ) in the hole‐transporting layer (HTL) and electron‐transporting layer (ETL).…”
Section: Introductionmentioning
confidence: 99%
“…S12B ) appears obviously in comparison with the c-SnO 2 and SnO 2 NPs film, which can be located at roughly 165.2 eV. This is generally assigned to the C–S–C (sulfide) or C–S–H (thiol) 57 , 58 , indicating the presence of sulfur species functionalities on SnO 2 QDs. Besides, we also detected the characteristic signals of Br 3 d core level located at a binding energy of 68.3 eV from SnO 2 QDs (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…[ 69 , 70 ] The lattice in these positions is extremely fragile and effortlessly destroyed by moisture and heat, thus the decomposition of perovskite film generally begins at the interface. [ 71 , 72 ] As shown in Figure S27 , Supporting Information, the moisture resistance of perovskite film has been reinforced by CN top modification. Except for passivating the defects at the surface, the incorporation of Cs + and Br − with smaller radii in the lattice also strengthens the ionic and covalent bonding of perovskite.…”
Section: Resultsmentioning
confidence: 99%